2008
DOI: 10.1364/oe.16.004582
|View full text |Cite
|
Sign up to set email alerts
|

Generation of 3.5W high efficiency blue-violet laser by intracavity frequency-doubling of an all-solid-state tunable Ti:sapphire laser

Abstract: In this paper, we report a high power, high efficiency blue-violet laser obtained by intracavity frequency-doubling of an all-solid-state Q-switched tunable Ti:sapphire laser, which was pumped by a 532 nm intracavity frequency-doubled Nd:YAG laser. A beta-BaB2O4 (BBO) crystal was used for frequency-doubling of the Ti:sapphire laser and a V-shape folded three-mirror cavity was optimized to obtain high power high efficiency second harmonic generation (SHG). At an incident pump power of 22 W, the tunable output f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…This work reports the hard-templating synthesis of carbon inverse replicas of SBA-15 and SBA-16 and their subsequent use for the preparation of the oxide−carbon nanocomposites, which after thermal treatment in air afford mesoporous mixed oxide materials. The XRD analysis of these oxide−carbon nanocomposites and the corresponding oxides revealed the presence of α-Al 2 O 3 and TiO 2 rutile phases as in sapphires, materials of great importance for optoelectronic and catalytic applications. ,, For some of these nanocomposites, the Magnéli phase (Ti 6 O 11 ) related to the rutile structure was found. This phase is composed of 2 Ti 3+ ions per unit formula, which were oxidized during calcination of these materials giving TiO 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work reports the hard-templating synthesis of carbon inverse replicas of SBA-15 and SBA-16 and their subsequent use for the preparation of the oxide−carbon nanocomposites, which after thermal treatment in air afford mesoporous mixed oxide materials. The XRD analysis of these oxide−carbon nanocomposites and the corresponding oxides revealed the presence of α-Al 2 O 3 and TiO 2 rutile phases as in sapphires, materials of great importance for optoelectronic and catalytic applications. ,, For some of these nanocomposites, the Magnéli phase (Ti 6 O 11 ) related to the rutile structure was found. This phase is composed of 2 Ti 3+ ions per unit formula, which were oxidized during calcination of these materials giving TiO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that synthesis conditions such as the presence of groups on the surface of carbons and the use of less polar solvents may be beneficial for the quality of the resulting materials . In general, the ordered mesoporous structures prepared by this route exhibited interesting physical properties, which are much different than the corresponding nonporous materials. ,,,, Note that other systems of interesting properties such as the Ti−Al mixed oxides, which are known for their optical, , dielectric, , and photocatalytic properties, , have not been prepared yet. Also, to the best of our knowledge, there are no reports on the use of carbons with the Im3m symmetry as hard templates for the synthesis of inorganic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Ti:Al 2 O 3 and Cr:LiSAF can emit laser at near infrared region and their wavelengths can be tuned around 0.8 µm, so cw or pulsed blue laser can be also achieved by frequency-doubling [24,25].…”
Section: Frequency-doublingmentioning
confidence: 99%
“…Nowadays, the development of compact and practical visible blue-violet lasers (380~430 nm) is attractive for a wide range of applications such as laser display, high-density optical storage, underwater communication, biology medicine, printing, marking and precision micro fabrications etc [1][2][3][4][5][6][7]. In order to get solid state coherent light in this spectral region, an effective way to generate high power blue-violet laser is by utilizing the nonlinear optical (NLO) crystals to frequency doubling Ti:sapphire laser [2, 4-6, 8, 9].…”
Section: Introductionmentioning
confidence: 99%